The Study of Competition Processes: Analysis of Enterprises’ Networks - Нина Николаевна Ивашиненко (Journal of Economic Sociology, 2010)
The variety of understanding the competition synthesizes is based on the concrete economic actor’s competitive strategy. Competitive strategy is the stable number of actions focused on the maximum effectively functioning of the enterprise on the market along with the understanding of the top-managers of these processes. The analysis of this understanding is the main aim of the paper. The key task was to disclose whether the enterprise strategy depends on how the competitors behave. The results proved that it is true, the impact is very strong. The network model allows us to reflect the process. The second question of the paper was – what is the interaction of the competing companies? It was found that in order to explain the processes we need as many networks as they have collaborations.  The depicting the centers of the network formation let us investigate the process deeper. The research was done in May-June of 2004, 120 managers were questioned; all of them were representing one of the companies in Nizhniy Novgorod.